Dynamics on next-neighbour distances in liquid and undercooled gallium. (15th November 2018) - Demmel, F
Abstract: Density fluctuations of liquid and 20 K undercooled gallium have been studied by neutron spectroscopy. The decay of density fluctuations has been recorded at the structure factor maximum over a wide temperature range up to twice the melting temperature. The amplitude of the scattering function falls off with rising temperature in a nonlinear way with a changing slope around . The derived generalized longitudinal viscosity shows an upturn with decreasing temperature in the same temperature range. This increase in viscosity can be understood that liquid gallium transforms from a more fluid liquid metal to a more viscous liquid metal in that temperature range upon cooling. The change in the amplitude shows a remarkable agreement with results from liquid aluminium, lead and rubidium. This study suggests a universal crossover in dynamics of liquid monatomic metals, despite the many peculiar properties of gallium.